Analisis Perbandingan Daya Dukung Tiang Tunggal Berdasarkan Hasil Data Sondir, N-SPT dan Data Laboratorium - Amalia, Ghina (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2024)
The need for boards is closely related to a building which not only functions as a residence but also as a place for almost all human activities such as offices, business premises and so on. The increase in population has caused the availability of land to become increasingly narrow, resulting in a large number of vertical building developments or high-rise buildings. In order to be able to fulfill the primary human need for shelter, these multi-storey buildings must not only provide comfort but also be safe. A safe building is obtained from accurate planning of all structural components of the construction, one of which is the foundation. There are many methods used to analyze the bearing capacity of soil, especially for pile foundations. The aim of this research is to compare the bearing capacity values of piles based on sondir data using the Mayerhoff and AokiDe Alencar, N-SPT methods with Mayerhoff, ReeseWright, ReeseO'nail and laboratory data on the 3-story Student Flats construction project at Indo Global Mandiri University. Based on the analysis that has been carried out, the carrying capacity results obtained by each method are different. This difference is because each method has its own efficiency and correction factor. From this analysis, the method that produces the lowest ultimate carrying capacity value is the method based on laboratory data, while the highest is the Mayerhoff method based on sondir data. The lab data method which produces the lowest ultimate bearing capacity will require a higher safety figure in planning pile foundations compared to other methods, so this method is the safest method to use in analyzing the bearing capacity of pile foundations.